2003
DOI: 10.1002/jctb.908
|View full text |Cite
|
Sign up to set email alerts
|

Ozonation of vinasse in acid and alkaline media

Abstract: The production of ethanol by fermentation and subsequent distillation generates wastewater known as 'vinasse'. This waste is highly polluting on account of its high organic load and antibacterial activity-which arises from the presence of phenolic compounds that reduce the efficiency of the detoxification treatments best suited to this type of waste (eg anaerobic digestion). This can be avoided by using a pre-treatment based on a chemical oxidant (ozone) at an acid or alkaline pH. Ozonation in acid media provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(8 citation statements)
references
References 33 publications
0
7
0
1
Order By: Relevance
“…Another issue that could have contributed to the low COD removal found in this study would be the likely low concentration of hydroxyl radicals at an acidic pH. In this case, the only oxidizing agent is likely to be molecular ozone (Mart´ın-Santos et al, 2003), which has been reported to have a lower reactivity for oxidizing several aliphatic compounds and carbohydrates (Benitez et al, 2000) compared with hydroxyl radicals.…”
Section: Resultsmentioning
confidence: 83%
“…Another issue that could have contributed to the low COD removal found in this study would be the likely low concentration of hydroxyl radicals at an acidic pH. In this case, the only oxidizing agent is likely to be molecular ozone (Mart´ın-Santos et al, 2003), which has been reported to have a lower reactivity for oxidizing several aliphatic compounds and carbohydrates (Benitez et al, 2000) compared with hydroxyl radicals.…”
Section: Resultsmentioning
confidence: 83%
“…COD removal by ozonation of WWs was found to be higher at alkaline pH than acidic pH; the opposite was found out for polyphenols removal which was higher at acidic pH [60,75]. Considering that molecular ozone prevails at acidic pH and radicals' formation is higher at alkaline pH, the selectivity of molecular ozone towards polyphenols is higher than the selectivity of the radicals for polyphenols.…”
Section: Winery Wastewater Treatment By Aopsmentioning
confidence: 87%
“…Vinasse is extremely polluting due its high organic load and antibacterial activity which arises from the presence of phenolic compounds (Martín Santos et al [2003]) that inhibit the PHA producing microorganism, H. mediterranei. Thus, pre-treatment for removal of polyphenolic compounds was necessary and the process proved to be effective as 25-50% of an acutely polluting waste like vinasse could be utilized.…”
Section: Discussionmentioning
confidence: 99%